Digital Transformation of the e-Mental App and Police Service Quality: Mental Health Role - Achmad Junaidi; Syahruddin Hattab; Muh Nawawi; Mohamad Irfan Mufti (Universitas Negeri Semarang, 2025)
Background - Digital transformation has become a strategic approach to improving public service performance, including in law enforcement institutions. The e-Mental application was introduced as part of digital innovation to enhance both the performance and mental health of police officers. However, the direct impact of digital transformation on service quality, particularly when considering internal psychological readiness, remains underexplored. Research Urgency - Given the growing demands for responsive public services and increasing work-related stress among officers, understanding how digital initiatives contribute to service quality and how mental health interacts with these effects is crucial for sustainable innovation. Research Objectives - This study aims to analyze the influence of digital transformation via the e-Mental application on the quality of police services, with mental health as a moderating factor. It also seeks to examine the effect of digital transformation on officers' mental health and how this moderates the relationship with service quality. Research Method - The research was conducted at the Police Resort (Polres) of Donggala Regency, Central Sulawesi. It involved 205 police officers across nine sectoral police stations (Polsek) as respondents for digital transformation and mental health variables, and 205 community members as evaluators of service quality. Data were analyzed using multiple linear regression with an interaction term. Research Findings - Digital transformation significantly improves both mental health (t = 6.250, p < 0.001) and service quality (t = 7.878, p < 0.001). However, mental health significantly moderates this relationship, weakening the effect of digital transformation on service quality (B = -0.019, t = -3.890, p < 0.001). Research Conclusion - Digital transformation alone is insufficient for improving service quality without psychological readiness and institutional support. Research Contribution - This study highlights the importance of integrating psychological well-being into digital innovation strategies, particularly in public service sectors like the police. Key words: Digital transformation, e-Mental app, mental health, Service quality.